Performa Ayam dan Kualitas Telur yang Menggunakan Ransum Mengandung Onggok Fermentasi dengan Neurospora crassa - . Nuraini; . Sabrina; S A Latif (Media Peternakan, 2008)
An experiment was conducted to determine the effect of feeding tapioca by-products fermented by Neurospora crassa on layer performances and egg quality. Two hundred layers were randomly allocated into 20 pens. This experiment was arranged in a completely randomized design with four dietary treatments: 0%, 10%, 20% and 30% tapioca by product fermented by N. crassa in the diets and five replications. Variable measured were feed comsumption, egg production, feed conversion, egg cholesterol and egg yolk colour. Results of the experiment indicated that feed comsumption, egg production, feed conversion, egg cholesterol and egg yolk colour were affected (P < 0.05) by using fermented tapioca by-product in the diets of layers. Results of Duncan multiple range test indicated that feed consumption, egg production, and egg yolk colour in D treatment (used 30% tapioca by-products fermented) were the highest compared to those other treatments, but the lowest on feed conversion and egg cholesterol. The conclusion of the experiment that tapioca by-products fermented by N. crassa can be used up to 30% in the diet of layer. Key words: tapioca by product fermented, Neurospora crassa ,layer performances, egg